Molybdenum(VI) dioxo complexes for the epoxidation of allylic alcohols and olefins - Pandhare, Swati L.; Jadhao, Rajesh R.; Puranik, Vedavati G.; Joshi, Pranaya V.; Capet, Frederic; Dongare, Mohan K.; Shubhangi B. Umbarkar; Michon, Christophe; Agbossou-Niedercorn, Francine (Journal of Organometallic Chemistry, 2014)
Several molybdenum(VI) dioxo complexes have been investigated as catalyst precursors for allylic alcohol epoxidation using mainly hydrogen peroxide as oxidant. All catalysts proved to be efficient and selective for the epoxidation of allylic alcohols provided the olefins were rather electron rich. Indeed, electron poor substrates could be converted selectively into the corresponding unsaturated aldehydes. A chiral dioxomolybdenum complex based on an optically pure tridentate Schiff base ligand was synthesized and characterized. Though that complex provided an efficient epoxidation catalyst for allylic alcohols and olefins, no chiral induction was observed. During the X-ray diffraction analysis, the cooling at 100 K led to the appearance of super-lattice reflections on diffraction patterns reflecting an ordering of the structure. Instead of one organometallic species observed at 298 K, three similar complexes of the same molecular structure could be observed in the asymmetric unit at 100 K. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Allylic alcohol; epoxidation; Molybdenum; Oxidation; Peroxide

Catalytic reductive deoxygenation of esters to ethers driven by hydrosilane activation through non-covalent interactions with a fluorinated borate salt - Rysak, Vincent; Dixit, Ruchi; Trivelli, Xavier; Merle, Nicolas; Agbossou-Niedercorn, Francine; Vanka, Kumar; Michon, Christophe (Catalysis Science & Technology, 2020)
We report the catalytic and transition metal-free reductive deoxygenation of esters to ethers through the use of a hydrosilane and a fluorinated borate BArF salt as a catalyst. Experimental and theoretical studies support the role of noncovalent interactions between the fluorinated catalyst, the hydrosilane and the ester substrate in the reaction mechanism.

Palladium supported on magnesium hydroxyl fluoride: an effective acid catalyst for the hydrogenation of imines and N-heterocycles - Kokane, Reshma; Corre, Yann; Kemnitz, Erhard; Dongare, Mohan K.; Agbossou-Niedercorn, Francine; Michon, Christophe; Umbarkar, Shubhangi B. (New Journal of Chemistry, 2021)
Palladium catalysts supported on acidic fluorinated magnesium hydroxide Pd/MgF2-x(OH)(x) were prepared through precipitation or impregnation methods. Applications to the hydrogenation of various aldimines and ketimines resulted in good catalytic activities at mild temperatures using one atmosphere of hydrogen. Quinolines, pyridines and other N-heterocycles were successfully hydrogenated at higher temperature and hydrogen pressure using low palladium loadings and without the use of any acid additive. Such reactivity trend confirmed the positive effect of the Bronsted and Lewis acid sites from the fluorinated magnesium hydroxide support resulting in the effective pre-activation of N-heterocycle substrates and therefore in the good catalytic activity of the palladium nanoparticles during the hydrogenations. As demonstrated in the hydrogenation of imines, the catalyst was recycled up to 10 times without either loss of activity or palladium leaching.

Silver dependent enantiodivergent gold(i) catalysed asymmetric intramolecular hydroamination of alkenes: a theoretical study - Dixit, Ruchi; Sharma, Himanshu; Agbossou-Niedercorn, Francine; Vanka, Kumar; Michon, Christophe (Catalysts, 2022)
We report a theoretical study of the first silver-dependent enantiodivergent gold-catalysed reaction. The combination of a single chiral binuclear gold(I) chloride complex and silver perchlorate catalyses the asymmetric intramolecular hydroamination of alkenes and affords both enantiomers of the products by applying a simple solvent change from toluene to methanol. A gold-silver chloride adduct that occurs only in methanol appears to control the enantioinversion. If one gold atom coordinates and activates the alkene moiety, the other gold is included in an adduct with silver chloride, which coordinates a methanol solvent molecule and further interacts with the amine function. If the use of toluene implies free anions and affords (S)-enantiomer, methanol allows a proximal interaction with the amine, leads to an opposite stereodifferentiation of the two diastereomeric intermediates during the final protodeauration step and results in the (R)-enantiomer.
Keywords: alkene; enantiodivergent catalysis; Gold; hydroamination; Silver

(NHC-olefin)-nickel(0) nanoparticles: an efficient and selective catalyst for hydrogenation reactions at low temperature and pressure - Avello, Marta G.; Singh, Geetika; Truong-Phuoc, Lai; Vidal, Loic; Papaefthimiou, Vasiliki; Chesse, Matthieu; Gruber, Nathalie; Chetcuti, Michael J.; Vanka, Kumar; Ritleng, Vincent; Pham-Huu, Cuong; Michon, Christophe (Journal of Catalysis, 2026)
The reduction of a NHC-cinnamyl nickel(II) organometallic complex through the use of different MeMgBr or MeMgCl reagents led to two types of NHC-olefin-coordinated nickel nanoparticles. Both of these unsupported nickel-NHC based nanomaterials behaved under hydrogen pressure as effective and selective catalysts operating at low temperature (<= 80 degrees C), pressure (<= 20 bar) and loading (<= 6 mol%) for the reductions of broad scopes of alkenes, alkynes, imines and heterocycles, including a challenging tetra-substituted alkene. Among these two nickel-NHC nanocatalysts, the one generated with MeMgCl showed a significant high catalytic activity with high yields and could stand the comparison with Raney nickel and state-of-the-art nickel nanocatalysts. For example, by studying the hydrogenation of 1-phenylcyclohexene in ethanol at 60 degrees C under 10 bar of H2, 3 mol% of this catalyst achieved the reaction within a single hour on a 5 mmol/0.8 g substrate scale with a yield of 96 %, a turnover number (TON) of 32 and a turnover frequency (TOF) of 32. Characterizations confirmed the coordination of the NHC-olefin ligands to the nickel nanoparticles, the reduced state of the nickel and the (poly-) crystallinity of the nanoparticles.
Keywords: alkenes; Alkynes; heterocycles; Hydrogenation; imines; N -heterocyclic carbene ligand; nanocatalysis; Nickel